2014
DOI: 10.3892/mmr.2014.3143
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin-6 is associated with epithelial-mesenchymal transition and survival rates in gallbladder cancer

Abstract: Abstract. The present study aimed to investigate the expression of interleukin-6 (IL-6) in gallbladder cancer (GBC) tissues and its correlation with survival rate. The association between IL-6 and epithelial-mesenchymal transition (EMT)-associated markers was also examined. Using immunohistochemistry, reverse transcription quantitative polymerase chain reaction (RT-qPCR) and western blot analysis, the protein and mRNA expression levels of IL-6, Twist, E-cadherin and Vimentin in 20 GBC tissues were analyzed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Moreover, IL-6 promotes the migration and invasion of multiple tumor cells, via the induction of EMT [39]. For example, the overexpression of IL-6 enhances the invasion and migration of gallbladder cancer cells, by stimulating EMT [40]. In this study, we found that exogenous IL-6 induced a significant downregulation of E-cadherin, and an enhancement of migration in the breast cancer cell line T47D.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, IL-6 promotes the migration and invasion of multiple tumor cells, via the induction of EMT [39]. For example, the overexpression of IL-6 enhances the invasion and migration of gallbladder cancer cells, by stimulating EMT [40]. In this study, we found that exogenous IL-6 induced a significant downregulation of E-cadherin, and an enhancement of migration in the breast cancer cell line T47D.…”
Section: Discussionmentioning
confidence: 57%
“…IL-6 is also a multi-functional cytokine secreted by a variety of cell types and is frequently involved in a series of physiological and pathological effects, including inflammation and fibrosis (30). Aberrant expression of IL-6 is associated with the poor prognosis of patients with glioma (31), and gallbladder and colon cancer types (32,33). The effects of p53 wt on the release of autocrine cytokines IL-10 and IL-6 and their protein expression levels in NCI-H1299 cells were also investigated in the present study, which indicated that p53 inhibits IL-10 in vitro autocrine and protein expression, but does not exert any influence on IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is difficult to identify the underlying mechanisms through which IL-6/IL-6R signalling regulate the carcinogenesis, progression and metastasis of ccRCC. An immunosuppressive effect on dendritic cells, a proinflammatory role through trans-signalling pathway, a growth factor effect and an epithelial–mesenchymal transition promoter role could all contribute to these observations; there are many works to accomplish before fully understanding the roles of IL-6 in RCC ( Cabillic et al , 2006 ; Jones et al , 2011 ; Wolf et al , 2014 ; Zhang et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%